Understand reverse logistics in cross-border e-commerce based on a case study of tmall global - Zhao, Menghan (Nanyang Technological University, 2020)
Cross-border e-commerce (CBEC) is a fast-growing sub-field in e-commerce. Compared with domestic e-commerce, it’s characterized by long shipping distances, long delivery time, customs clearance and import duties. Due to logistical complexity, customer returns in cross-border e- commerce has long since been an aching issue. Based on a case study of the largest CBEC import platform in China, this project analyses the logistics modes and return regime in use for the dominant platform in China. Suggestions were made on how to reduce reverse logistics related customer complaints from a system view.